LEADERSHIP INITIATIVES IN TERMS OF NON-POSITONAL OF VOCATIONAL SCHOOL STUDENTS - Nuri BALOĞLU; Onur DOĞAN (International Journal of Eurasia Social Sciences, 2018)
In this study, it was tried to find out how Vocational School students are in terms of non-positional leadership initiatives. The research was designed in accordance with the qualitative research paradigm. The study group consisted of 14 students in a vocational college of a university in Central Anatolia, 3 of which were technical and 4 of which were social. Measurement group based sampling technique was used for purpose sampling methods in the study group. The data were collected using a semi-structured interview form prepared by the researchers. Analysis was done by content analysis technique. Findings showed that non-positional leadership initiatives in students were problem solving in academic purposes and socio-cultural, sportive activities. Average number of non-positional leadership initiatives the student had made during their learning period was two on average. The number of leadership initiatives that the same students may want to do, but cannot do, is fewer than the number of initiatives they have undertaken. Students are particularly concerned with their peer groups and managers who do not want to take risks as an obstacle to leadership initiatives. Findings obtained within the scope of the research were discussed on the basis of the related literature and some suggestions based on findings were also developed.